The last gift - Gurnah, Abdulrazak (London Bloomsbury, 2011)
Abbas has never told anyone about his past-before he was a sailor on the high seas, before he met his wife Maryam outside a drugstore in Exeter, before they settled into a quiet life with their children, Jamal and Hanna. Now, at the age of sixty-three, he suffers a collapse that renders him unable to speak about things he thought he would one day have to.
Keywords: Families, Black--England--Fiction.